2014
DOI: 10.1080/10255842.2014.916699
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of Stryker Xia pedicle screw in artificial bone samples with and without supplemental cement augmentation

Abstract: A validated, using in vitro biomechanical testing, finite element model was used to evaluate the affects of (1) cement augmentation and (2) an intact posterior cortex in osteoporotic bone. The presence of augmentation and/or a posterior cortical cortex increased the stabilization of the pedicle screw 2-5 fold. Placement of cement influenced failure load and toggle; with distal placement having the largest increase in failure load and decrease in cephalad-caudad toggle. The presence of posterior cortex caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…45 In addition, concentrating cement around the tips of the screws seems to maximize this enhancement effect. 46 There are some theoretical risks when using cement augmentation of pedicle screws. Those include cement extravasation into the venous system with risk of embolism, 47 extravasation into the spinal canal with risk of neurological injury, or extravasation into an adjacent disc.…”
Section: Cement Augmentation Of Screwsmentioning
confidence: 99%
“…45 In addition, concentrating cement around the tips of the screws seems to maximize this enhancement effect. 46 There are some theoretical risks when using cement augmentation of pedicle screws. Those include cement extravasation into the venous system with risk of embolism, 47 extravasation into the spinal canal with risk of neurological injury, or extravasation into an adjacent disc.…”
Section: Cement Augmentation Of Screwsmentioning
confidence: 99%
“…Similarly, there are also a lot of numerical results from the finite element analysis. The finite element analysis by Ferris et al demonstrated that placement of cement influenced failure load and toggle, with distal placement having the largest increase in failure load and decrease in cephalad-caudad toggle [ 20 ]. Polikeit et al investigated the effect of cement augmentation on an osteoporotic fusion lumbar spinal unit by using finite element analysis.…”
Section: Introductionmentioning
confidence: 99%